P119 Characteristics and treatment of fibrosclerosing orbital inflammatory disease. (20th April 2020) - Thanopoulou, Vasiliki; Weller, Alexander; Nigar, Ezra; Marais, Joseph; Lee, Vickie; Marjanovic, Branka; Ahmed, Abdul; Balasundaram, Indran; Hamdulay, Shahir
Abstract: Background: Orbital inflammatory disease (OID) encompasses a group of disorders which affect the orbit and neighbouring areas. Several multi-system inflammatory diseases including small vessel vascuilitides, Sarcoidosis and IgG4 disease can manifest as an OID. Treatment generally includes steroid therapy in combination with conventional immunosuppressant's, cyclophosphamide or rituximab. Herewith we describe a series of non-vasculitic, fibroinflammatory OID. Methods: We retrospectively reviewed records of 5 patients referred to rheumatology with inflammatory OID after malignancy, infection and Graves' ophthalmopathy were excluded. General demographics, histology, MRI and treatment responses were reviewed. Results: Patients were generally female (4:1) and of a young age (range 33-54). Proptosis and diplopia were the key symptoms with occasional sino-nasal symptoms. Inflammatory markers on presentation were marginally raised (CRP mean 11, ESR mean 37). All patients were negative for autoantibodies and had normal serum IgG4 levels. MRI showed fibrotic mass lesions in all cases with bone erosion/ destruction in 2 cases. Biopsy showed fibrosclerosis mixed with chronic inflammatory cells. 3 cases stained positive for IgG4 cells but only one of them achieved diagnostic levels (case 3). All patients were initially treated with high dose steroids (prednisolone 1mg/kg or IV methylprednisolone (MP)) with either methotrexate or cyclophosphamide (1g EUVAS protocol). Highly resistant cases were treated with rituximab (total 2g). There was a good clinical response to treatment in all cases but in 4 patients residual fibrosis persisted on follow-up MRI (Table 1). Conclusion: We describe a series of fibrosclerosing OID with histology like IgG4 disease, but with normal serum IgG4 levels and negative tissue immunofluorescence (IF) in some cases. Most cases will respond well to steroids and second-line therapy, but residual fibrosis may persist with mild clinical sequelae. Early recognition and intensive therapy may minimise fibrotic complications. Disclosures: V. Thanopoulou None. A. Weller None. E. Nigar None. J. Marais None. V. Lee None. B. Marjanovic None. A. Ahmed None. I. Balasundaram None. S. Hamdulay None.